Wirausaha Muda Mandiri sebagai Penggerak Ekonomi Bangsa - Revanza Syach; Sindroi Anuegrah Ndraha; Bagas Wahyu Dewanta; Ari Anggarani Winadi Prasetyoning Tyas (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
This community service program, focusing on Entrepreneurship Education, is designed to foster a new generation of independent, science- and technology-based entrepreneurs. The theme was chosen based on the current social reality, where the high number of workers is not commensurate with the availability of jobs, thus triggering rising unemployment rates. The program's partner, SMK Negeri 2 Jakarta, faces major challenges in the form of limited extracurricular activities that can support the development of students' entrepreneurial spirit, as well as students' limited knowledge and skills in understanding the business world comprehensively. This condition results in a low number of graduates choosing entrepreneurship as a career path. Therefore, the goal of this program is to improve entrepreneurial competency among students, with the specific goal of forming a community of independent students with the practical skills to manage their own businesses. Activities include seminars, training, and intensive entrepreneurial mentoring with SMK Negeri 2 Jakarta as a partner. The program was attended by 110 students and 15 teachers and educational staff. To assess the success of the program, an evaluation was conducted through the distribution of questionnaires to measure participants' level of understanding and by comparing business results before and after the program was implemented. The final results showed a significant increase in students' understanding and entrepreneurial skills, which was reflected in the increase in sales of entrepreneurial products and services in the partner school environment.